2018
DOI: 10.1038/s41416-018-0352-y
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-alpha promotes immunosuppression through IFNAR1/STAT1 signalling in head and neck squamous cell carcinoma

Abstract: BackgroundAn immunosuppressive microenvironment is critical for cancer initiation and progression. Whether interferon alpha (IFNα) can suppress immune and cancer cells and its involved mechanism still remain largely elusive.MethodsWe examine the expression of interferon alpha/beta receptor-1 (IFNAR1), CD8, CD56 and programmed death ligand 1 (PDL1) in head and neck squamous cell carcinomas (HNSCC). The effect of IFNα on PDL1 and programmed cell death protein 1 (PD1) expression in tumour cells and immune cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 51 publications
2
42
0
Order By: Relevance
“…Last, we demonstrated that lncMX1-215 acts as a tumor suppressor during tumor progression. This study elucidates Several cells and cytokines have been reported to be involved in immunosuppression, such as tumor-associated macrophages [24], cancer-associated fibroblasts [25], myeloid-derived suppressor cells [26], regulatory T cells, TGF-β [27], IL-6 [28], and interferon [9]. Clarifying the regulatory networks involved in immunosuppression formation in the tumor microenvironment is critical and will contribute to clinical treatment with ICBs.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Last, we demonstrated that lncMX1-215 acts as a tumor suppressor during tumor progression. This study elucidates Several cells and cytokines have been reported to be involved in immunosuppression, such as tumor-associated macrophages [24], cancer-associated fibroblasts [25], myeloid-derived suppressor cells [26], regulatory T cells, TGF-β [27], IL-6 [28], and interferon [9]. Clarifying the regulatory networks involved in immunosuppression formation in the tumor microenvironment is critical and will contribute to clinical treatment with ICBs.…”
Section: Discussionmentioning
confidence: 87%
“…NK cell lysis assays were performed as previously described [9]. After being transfected for 24 h, HN4 and Cal27 cells were seeded in 96-well plates at 4~6 × 10 3 cells per well.…”
Section: Nk Cell Lysis Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Combinational treatment of IFN-α and IFN-γ inhibit growth and induces OC cells [ 59 ]. IFN-α signaling is mediated through a receptor complex of interferon-alpha/beta receptor-1 (IFNAR1) and IFNAR2, and these two subunits are significantly associated with an immunosuppressive environment in cancer [ 60 ]. IFITs are interferon's stimulated genes and identified as IFIT1, IFIT2, IFIT3, and IFIT5 in humans [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…1) (Ragimbeau et al, 2003;Uz e et al, 2007;Wallweber et al, 2014). In basal conditions the IFNAR1/2 cytoplasmic tails remain bound, in an inactive conformation, by the JAK proteins (Gui et al, 2017;Ma et al, 2019;Ragimbeau et al, 2003;Teijaro et al, 2016). Engagement by IFNα/β causes dimerization of IFNAR1/2 receptor chains thereby triggering the JAK/TYK2 kinase domains to undertake activation directed through their trans-phosphorylation (Pfeffer et al, 1997;Schneider et al, 2014).…”
Section: Sensing Of Type I Ifnsmentioning
confidence: 99%